2017
DOI: 10.22146/jpti.17542
|View full text |Cite
|
Sign up to set email alerts
|

Infeksi Ganda Begomovirus Dan Crinivirus Pada Tanaman Tomat Di Kabupaten Magelang , Jawa Tengah (Double Infections of Begomovirus and Crinivirus on Tomato Plants at Magelang Regency, Central Java)

Abstract: INTISARIPenyakit kuning pada tanaman tomat (Lycopersicon esculentum) telah ditemukan sejak tahun 2006 di Jawa Tengah, Indonesia. Epidemi penyakit tersebut terutama berkaitan dengan keberadaan dua spesies whitefly (Trialeurodes vaporariorum dan Bemisia tabaci). Gejala utama yang ditemukan adalah daun-daun pada tanaman bagian bawah berwarna kuning sedangkan daun daun pada tanaman bagian atas menunjukkan gejala keriting. Adanya gejala campuran pada satu individu tanaman maka perlu dideteksi penyebabnya untuk peng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…However, the sequencing of the full DNA-A of Begomovirus needs to be carried out to achieve precise and accurate identification results (Hernandez-Zepeda et al, 2007). Previous studies also used this method for the quick identification of Begomovirus in melon (Subiastuti et al, 2019), tobacco (Widarta et al, 2017), tomato (Kusumaningrum et al, 2015), bitter melon (Tiwari et al, 2010), and mung bean (M. N. Islam et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the sequencing of the full DNA-A of Begomovirus needs to be carried out to achieve precise and accurate identification results (Hernandez-Zepeda et al, 2007). Previous studies also used this method for the quick identification of Begomovirus in melon (Subiastuti et al, 2019), tobacco (Widarta et al, 2017), tomato (Kusumaningrum et al, 2015), bitter melon (Tiwari et al, 2010), and mung bean (M. N. Islam et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The application of polymerase chain reaction (PCR) techniques to detect viral infections in plants is a sensitive, reliable, reproducible, and effective method, especially for large samples (Lopez et al, 2008). Previous studies reported the use of molecular methods to detect Begomovirus infections in chilies and eggplants (Maruthi et al, 2007), okra (Venkataravanappa et al, 2018), and tomatoes (Kusumaningrum et al, 2015). The present study was conducted to determine the effect of using screen houses in chili (Capsicum frutescens L. 'Cempluk') cultivation on the severity of Begomovirus infection and the diversity of Begomovirus coat proteins that cause yellow leaf curling in chilies using molecular methods.…”
Section: Introductionmentioning
confidence: 99%
“…Sampling was conducted in 2018. Ketep was chosen as a sampling site because it is one of the horticulture produc tion areas in Central Java and reported as endemic area of begomovirus infections, as reported by Kusumaningrum et al (2017). Symptom appearance of the sample was mo saic, leaf yellowing, stunting, which are common symp toms of begomovirus infection (Figure 1).…”
Section: Sampling Locationmentioning
confidence: 99%
“…Diseases caused by begomovirus in fection initially only occurred in the lowlands. But in re cent years, the disease is also found in the highlands area (Kusumaningrum et al 2017). Besides, diseases caused by begomovirus have also been reported affecting new hosts, including eggplant and luffa (Kintasari et al; Giovanni et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Secara umum, peningkatan keparahan penyakit akan terjadi apabila adanya koinfeksi dari satu atau dua virus dibandingkan apabila diinfeksi oleh satu virus (Choi et al, 2002;Kusumaningrum et al, 2015;Syller, 2012). Akan tetapi, infeksi ganda dapat menimbulkan tekanan pada salah satu virus (Dufresne et al, 1999: Poolpol andInouye 1986;Syller dan Grupa, 2016).…”
Section: Pembahasanunclassified